ANALYSIS OF ACCESSIBILITY TO JOBS BY CAR IN THE CITY OF SYDNEY, AUSTRALIA - Suthanaya, Putu Alit (Jurnal Ilmiah Teknik Sipil; Vol. 10, No. 2 Juli 2006)
Low density urban sprawl generates a greater need to travel than more compact structures of mixed land uses in which the physical separation of activities is small. One way to reduce travel needs would be to bring homes, jobs, and service together in a relatively compact urban centre to achieve a high level of accessibility with little need for movement. Recently, research has focused on the debate of the urban form contribution to reduce urban travel and car dependence and to achieve a more sustainable city. One variable to define urban form is accessibility to jobs. Accessibility concept can be used to analyze relative job-housing location. Using journey-to-work (JTW) Census data over a 35-year period from 1961 to 1996 in Sydney, this paper analyze accessibility to jobs in Sydney, Australia by applying several methods such as dispersal index, Z-score, lorenz curve and Hansen Index. The results indicated that both housing and employment have moved away from the CBD towards the outer areas. Decentralization of both residential workers and employment was followed by an increasing use of car. Because the employment location in the outer ring is much easier to reach by car, this leads to an increasing car dependence by residents. If the decentralization trend continues into the future without a change to the public transportation service, it is expected that the proportion using car will increase by about 12.7 percent of the 1981 share. The mean trip length by car is predicted to increase by about 20.5 percent from its 1981 value. This finding indicates that the change in the relative jobs-housing location was followed by a change in travel patterns.
Keywords: accessibility, jobs, private car.